Assessing Differential Knowledge and Attitude Level Apropos Eco-friendly Practices (EFP) Among the Vegetable Growers - Neeraja Patel and Sandeep Chouhan, (Indian Journal of Extension Education, 2017)
Management of eco-friendly farming is focussed on the whole farm system and its interactions with climate, environment,social as well as economic conditions, rather than considering the farm as individual enterprises. The study was conductedin Indore district of Madhya Pradesh with 120 vegetable growers of 10 villages which were selected randomly. All theselected farmers were interviewed personally using a well-structured interview schedule. For analysis of collected data,descriptive statistics (frequency and percentage) and analytical statistics were used. The finding reveals that the higherpercentage of vegetable growers (64.17%) had low knowledge of technology. This may be due to lack of awareness ofscientific technology and lack of exposure of about improved technologies in agriculture. Majority (59.16 %) ofvegetables growers were in the category of favourable attitude towards use of eco-friendly management practices.